An Appraisal of Skill Gaps in Bioinformatics Education - Sharma, Smriti; Bhatia, Vinayak (Current Bioinformatics, 2021)
There has been an exponential rise in the field of bioinformatics in the last decade. The specialists of this field need to be well versed in computing, statistics, and mathematics, along with expertise in biological sciences. This review is an attempt to understand the existing skill gaps in the education of bioinformatics globally and to give the policy developers some indicators while designing the curriculum of the bioinformatics course. Authors have found that the pace with which this field is developing is not commensurate with the training and education efforts at the university level globally. But, on a positive note, academia and industry both seem to recognise this lag, therefore, efforts are being made in this direction. This review also summarizes the distinctive features needed to integrate bioinformatics in education for curriculum designing, teaching, and learning methods.
Keywords: educational technology